Steering the Implementation of Urban Sustainability Projects: Implications for Policy - Di FOGGIA, Giacomo (Journal of Environmental Management and Tourism, 2016)
Air pollution and traffic congestion concerns many cities around the world, no exception for Europe where almost a third of urban citizens must cope with worrying levels of air pollution that exceed some of the European air quality standards. Urban deliveries generally contribute to problems such as pollution, noise, congestion and unsafe environments within cities. Conversely, if distribution vehicles would be used more efficiently, it should theoretically be possible to reduce the amount of vehicles in city centers. To make this to happen new solutions aimed at tackling long-standing ecological crises with rather innovative approach are required. Although with positive environmental and socio-economic impacts, many projects struggle when it comes to define a long-term plan for the development. In most cases, in fact, they cannot be self-financing because of economics of scale or scope. This paper proposes a framework aimed at providing policy recommendations when it comes to the development of sustainability projects in urban areas focusing of environmentally friendly vehicles. The paper outlines a number of available policy tools to tackle the organizational, technological economic difficulties. This is done taking into consideration the infrastructure required, the enabling technology and the governance in an effort to provide suggestions to set viable business model.
Keywords: market-based instruments; urban sustainability; regulation; environmental policy; sustainable mobility